Levels and mechanisms of insecticide resistance in Southeast Asian Aedes aegypti: a scoping review - Indri Erisa; Nurlita Indah Arini; Henry Setyawan Susanto; Mateus Sakundarno Adi (Berita Kedokteran Masyarakat, 2026)
Purpose: To map published evidence on phenotypic insecticide resistance and resistance mechanisms in Aedes aegypti across Southeast Asia. Methods: This scoping review followed the JBI methodology and PRISMA-ScR reporting guidelines. PubMed, Scopus, and ProQuest were searched on September 11, 2025, for English-language primary studies published from January 1, 2015, to September 11, 2025. We included studies from Southeast Asian countries that used field or semi-field Aedes aegypti populations and reported WHO tube test or CDC bottle bioassay results, resistance mechanisms, or both. Results: We identified 416 records, removed 84 duplicates, screened 332 titles and abstracts, assessed 56 full texts, and included 26 studies from eight countries. Indonesia contributed 12 studies, and Malaysia, 6. Of the 20 studies that conducted WHO or CDC bioassays, all reported resistance to at least one insecticide, with outcomes varying by insecticide and site. Pyrethroids were the most frequently assessed class and the most commonly reported as resistant. Mechanisms were reported in 23 studies, most often VGSC kdr mutations V1016G (73.9%), F1534C (47.8%), and S989P (34.7%). Metabolic mechanisms were also reported, including elevated esterases (26.1%), oxidases or mixed-function oxidases (17.3%), cytochrome P450 monooxygenases (13%), and glutathione S-transferases (13%). No included studies reported cuticular or behavioral resistance. Conclusion: Insecticide resistance in Southeast Asian Aedes aegypti is widespread but heterogeneous, reflecting both target-site and metabolic mechanisms. Standardized, routine surveillance that links bioassays with mechanism testing is needed to guide insecticide choice, rotation, and integrated vector management.